Polymerase Chain Reaction for Detection and Genotyping of Molluscum Contagiosum Virus in Diyala Province - Mohammed Khalifa AL –Azawi (Diyala Journal of Medicine, 2019)
Background: Molluscum contagiosum virus (MCV): is a viral skin infection which may infect themucous membrane and skinoccasionally, It is caused by Molluscipox virus from family Poxviridae. Molluscum contagiosumvirus (MCV) was first described and later assigned its name by Bateman in the beginning of the nineteenth century.